MINERALOGICAL AND CHEMICAL COMPOSITION EVALUATION OF LIGNITE COAL FROM IHIOMA ORLU, IMO STATE OF NIGERIA. - G.C. Anyanwu,; EVANGELINA. O., OHAERI (IJRDO-Journal of Applied Science, 2022)
A sample of Ihioma lignite coal in Orlu Local Government Area of Imo Stat, Nigeria, was analyzed to finding its chemical and mineralogical composition using particle size distribution, XRD-EDS, proximate, ultimate, mineral composition analysis. Particle size distribution  recorded less than 1% values with mesh size of the sample, the proximate analysis recorded 6.0%,4.0%,38.5%,51.5% of moisture, ash content, volatile matter and fixed carbon, while ultimate analysis recorded 2.0%,4.0%,1.064%,64.6% of oxygen, hydrogen, nitrogen and carbon respectively. The mineral composition indicated 20.5% sodium and 6.6% of silicon as highest composition while 0.3% sulphur and 0.43% aluminum recorded lowest mineral composition of the coal sample. Also 70.81% of FeO3 and 68.0% of CaO3 chemical compositions were fully distributed, while 0.01% of TiO2 and 0.04 of K2O were relatively less distributed in the coal sample. The mineralogical analysis showed the presence of hematite as the major mineral while quartz, albite and trace metals of metakaolin were noted as minor minerals in the sample. This coal has index evaluation maturity, quality potential, environmental friendliness and ignition characteristics. It can also be useful in many ways such as in ceramics, pottery, and in manufacturing of ornamental stones.